Raised CA19-9 in Autoimmune Pancreatitis - Sundaram, Sridhar; Gupta, Deepak Kumar (Journal of Digestive Endoscopy, 2020)
Autoimmune pancreatitis (AIP) is a known autoimmune disorder of the pancreas, with a clinical presentation similar to that of carcinoma of the pancreas. CA19-9 levels can be the distinguishing feature between the two disorders. In rare instances, CA19-9 may be elevated in AIP. Elevation of levels of more than 1,000 U/mL has been reported in only one case series previously. Here we report a rare instance of CA19-9 more than 1,000 U/mL in a case of AIP and its subsequent management.
Keywords: autoimmune pancreatitis; CA19-9; carcinoma of the pancreas